Food biosensors - Ahmen, Minhaz Uddin; Zourob, Mohammed; Tamilya, Eiichi (Royal Society of Chemistry, 2017)
Covering all aspects of food biosensors, from how they function to the latest market applications, this book is essential reading for both new comers and experts in this field.
Obsahuje index.
Keywords: biosenzory; potravinářský průmysl; analýza potravin; biosensors; food industry; food analysis; kolektivní monografie; elektronické knihy; collective monographs; electronic books